Rhinonyssus nenecoi sp. nov. (Mesostigmata: Rhinonyssidae); a new nasal mite from Daption capense (Procellariiformes: Procellariidae) - Gastal, Silvia Bainy; Mascarenhas, Carolina Silveira; Bugoni, Leandro (Zootaxa, 2023)
Parasitic nasal mites have been surveyed in a range of vertebrate hosts, but only two species of Rhinonyssidae have been described from procellariiform seabirds. We here describe Rhinonyssus nenecoi sp. nov., from Cape petrels, Daption capense (Procellariidae), collected in Rio Grande do Sul State, southern Brazil. The new species is morphologically most similar to R. procellaricus and R. pluvialis differing mainly by a strongly sclerotised podosomal shield with four pairs of setae, covering more than half of the idiosoma; a podosomal shield with a V-shaped posteromedial projection; an irregularly-shaped sternal shield; and a ventral opisthosoma with 3–4 pairs of setae.